Surgical treatment of pediatric forearm fractures with intramedullary nails: is it a disadvantage to leave the tip exposed? - Ozturk, Ibrahim A.; Engin, Muhammed C.; Dincer, Recep; Kose, Ahmet; Topal, Murat (Ovid Technologies (Wolters Kluwer Health), 2020)
Elastic intramedullary nailing is the main treatment method in the surgical treatment of pediatric forearm fractures. In this study, we compared the clinical outcomes of intramedullary nailing of forearm fractures with leaving the tips exposed and with placing the tip of the nails under the skin. We aimed to present the clinical outcomes of intramedullary nailing and determine the advantages and disadvantages of leaving the tips of the nails exposed. One hundred and ninety-two children with both-bone forearm fracture who were treated with titanium elastic nailing (TEN) in the Department of Orthopedics at Erzurum Regional Training and Research Hospital between January 2009 and December 2016 were included in the study. All cases had been followed up for at least 1 year. The tips of the TENs were left exposed in 74 and buried subcutaneously in 118 children. Union was achieved in all cases. Delayed union was observed in just one case. Skin irritation was observed in 11 (5.7%) of the exposed TEN cases. Superficial infection developed in two (1%) cases with exposed TEN tips. Migration developed during the follow-up of 11 (5.7%) cases with buried tips. The mean time to removal of TEN was 7.9 weeks in cases with exposed and 26.2 weeks in cases with buried cases. Refracture was observed in six buried (3.1%) cases and four exposed TEN (2.1%) cases in the first year after the removal of the nails. Perfect outcomes were achieved in 146 (76%) cases and good outcomes in 36 (19%) cases in our study. On comparing the rate of complications and clinicaloutcomes, leaving the TEN exposed seems to be safe.
Keywords: Fracture Healing; Male; Adolescent; Bone Nails; Ulna Fractures; Fracture Fixation, Intramedullary; Postoperative Complications; Treatment Outcome; Humans; Female; Child; Radius Fractures; 3. Good health